Hydrodynamics of a reactor for thermocatalytic oxidation of sewage sludge. (15th April 2023) - Klenov, O.P.; Dubinin, Yu.V.; Yazykov, N.A.; Yakovlev, V.A.
Graphical abstract: Highlights: The creation of a fluidized bed in a reactor for thermocatalytic oxidation of sewage sludge using simple distribution system has been studied. CFD modeling based on the 3D Navier-Stokes equations and Eulerian–Eulerian approach was performed. Air cavities were formed under a distribution system consisting of sparger pipes. The uneven distribution of the flow through the sparger reaches 15%, however, this is compensated by the mutual arrangement of the pipes. Abstract: One of the promising methods for the disposal of municipal sewage sludge is its thermocatalytic oxidation in fluidized bed reactors. An important factor determining the stability of the operation of fluidized bed reactors is the uniform introduction of the air flow, which, on the one hand, fluidizes a bed of catalyst solid particles and solid sewage sludge, and, on the other hand, the oxygen of the air flow serves as an oxidizing agent in chemical reactions occurring in the reactor. A pilot plant for thermocatalytic oxidation, created according to the technology of the Boreskov Institute of Catalysis, is operated at JSC Omskvodokanal (Omsk, Russia). The plant's capacity is 50 thousand tons per year of mechanically dehydrated sludge with a water content of 70–80 wt%. The cross-sectional area of the sludge combustion zone is 3.8 m 2 . The heat flow from the incoming sludge (physical heat and heat of combustion) is 6527000 kcal/h. The air flow was introduced into the fluidized bed reactor with a sparger of 6 perforated pipes arranged horizontally and in parallel. The purpose of this work is to investigate the influence of inlet conditions on fluidized bed hydrodynamics. The results obtained showed that despite the uneven distribution of air flow through the holes of the sparger tubes, each pair of adjacent sparger tubes mutually compensate each other in terms of air flow per unit area of the cross section of the reactor. It is also shown that during the operation of the reactor, air cavities are formed under the sparger pipes, which are practically free of solid particles. The position of such air cavities and their approximate volume are stationary in time for a developed fluidized bed, and the volume of the cavities is approximately proportional to the dimensions of the respective sparger tubes. These air cavities periodically eject bubbles into the overlying portions of the fluidized bed. The dimensions of the bubbles are comparable to the transverse dimensions of the pipes.